Intracoronary nicorandil induced hyperemia for physiological assessments in the coronary artery lesions - Yang, Xia; Yu, Qiang; Yang, Junjie; Guo, Jun; Jin, Qinhua (Frontiers in Cardiovascular Medicine, 2022)
Objective: Maximal hyperemia is a key element of invasive physiological examination. The aim of this study was to investigate the efficacy and safety of intracoronary (IC) nicorandil in comparison to adenosine 5'-triphosphate （ATP）intravenous (i.v.) injection for fractional flow reserve (FFR) measurement in coronary artery lesions. Methods: 46 patients who measured FFR were enrolled in this study, including 51 lesions. Hyperemia was induced by bolus 2mg nicorandil and ATP (40mg ATP + 36ml saline, weight x 10 ml/hour）for FFR measurement. The safety and efficacy of IC nicorandil were evaluated. Results: The mean FFR value measured by nicorandil and ATP was 0.810±0.013 and 0.799±0.099，p<0.001 respectively. There was a strong correlation about FFR measured by nicorandil and ATP(r=0.983，R2=0.966, FFRnicorandil=0.937xFFRATP+0.061). The rate of FFR≤0.75 in nicorandil and ATP group was 31.37% vs 35.29% respectively(p=0.841)，the consistency rate was 96.08%；FFR≤0.8 rate was 41.18% and 43.14% respectively(p=0.674), consistency rate 90.20%. The FFR value by nicorandil were among 0.79-0.82 in 5 lesions which existed inconsistency according to FFR≤0.8. The blood pressure change by nicorandil and ATP was 12.96±6.83mmHg and 22.22±11.44mmHg (P<0.001); heart rate change was 2.43±1.31 and 6.52±2.87beats/min(P<0.001); PR interval changes was 6.0(1.0-11.0) and 9.0(2.0-19.0)ms(P<0.001). Visual analogue scale (VAS) scores in nicorandil group were all in 0-2, while in ATP group were mostly in 3-5. Conclusions: IC bolus of nicorandil (2mg) infusion induces a stable hyperemia, and it could be considered as an alternative drug to ATP for FFR measurement with lower side effect profile in most patients.